Iron-Loaded Magnetic Nanocapsules for pH-Triggered Drug Release and MRI Imaging - Chen, Hongyu (Chemistry of materials : a publication of the American Chemical Society, 2014)
Magnetic nanocapsules were synthesized for controlled drug release, magnetically assisted delivery, and MRI imaging. These magnetic nanocapsules, consisting of a stable iron nanocore and a mesoporous silica shell, were synthesized by controlled encapsulation of ellipsoidal hematite in silica, partial etching of the hematite core in acid, and reduction of the core by hydrogen. The iron core provided a high saturation magnetization and was stable against oxidation for at least 6 months in air and 1 month in aqueous solution. The hollow space between the iron core and mesoporous silica shell was used to load anticancer drug and a T1-weighted MRI contrast agent (Gd-DTPA). These multifunctional monodispersed magnetic "nanoeyes" were coated by multiple polyelectrolyte layers of biocompatible poly-l-lysine and sodium alginate to control the drug release as a function of pH. We studied pH-controlled release, magnetic hysteresis curves, and T1/T2 MRI contrast of the magnetic nanoeyes. They also served as MRI contrast agents with relaxivities of 8.6 mM-1 s-1 (r1) and 285 mM-1 s-1 (r2)